Correction: Ni–Cu alloy nanoparticles loaded on various metal oxides acting as efficient catalysts for photocatalytic H2 evolution. Issue 59 (28th June 2015) - Yamada, Yusuke; Shikano, Shinya; Fukuzumi, Shunichi
<x xml:space="preserve">Abstract</x> Correction for 'Ni–Cu alloy nanoparticles loaded on various metal oxides acting as efficient catalysts for photocatalytic H2 evolution' by Yusuke Yamada et al., RSC Adv., 2015, 5, 44912–44919.